2017
DOI: 10.5535/arm.2017.41.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Exercise Training for High-Risk Cardiac Patients

Abstract: ObjectiveTo examine the effect and safety of cardiac rehabilitation (CR) program in high-risk cardiac patients and compare these results to those of control CR participants without high-risk criteria.MethodsA total of 12 high-risk cardiac patients were recruited as subjects. The high-risk criteria were: advanced heart failure with left ventricular ejection fraction (LVEF) of less than 30%, a recent history of cardiac arrest or dangerous arrhythmia, and cardiac device insertion. Another 12 CR participants witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Additionally, the author also confirmed that other echocardiographic parameters, LVESD and LVEDD, showed no significant difference in either group ( Figure 3 and Table 4 ), which correlates with the results of previous studies in high-risk patients [ 31 ]. One study that was conducted in Japanese patients revealed that an increased epicardial adipose tissue volume may affect the hemodynamics and CPF by decreasing the peak oxygen uptake [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the author also confirmed that other echocardiographic parameters, LVESD and LVEDD, showed no significant difference in either group ( Figure 3 and Table 4 ), which correlates with the results of previous studies in high-risk patients [ 31 ]. One study that was conducted in Japanese patients revealed that an increased epicardial adipose tissue volume may affect the hemodynamics and CPF by decreasing the peak oxygen uptake [ 32 ].…”
Section: Discussionsupporting
confidence: 88%
“…At the literature, although Paul-Labrador et al 11 identified reasonable levels of associations ( r = 0.19–0.47), both Vongvanich et al, 10 Paul-Labrador et al, 11 and Choi et al 13 did not identify significant associations between the cardiac risk stratification classified by the protocols used in this study and the occurrence of major complications that influence individual’s hemodynamics either. These studies considered sudden death, complex arrythmias and cardiopulmonary arrest as important complications.…”
Section: Discussionmentioning
confidence: 53%
“…ejection fraction value, ischemic intensity, degree of myocardial dysfunction) are specifics and differ from one to another. 2,3,813…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant between-group differences in cardiorespiratory fitness at 12 and 24 months, indicating there was no training effect. In recent studies both moderate and high intensity training increased VȮ 2max , but the VȮ 2max was measured immediately after the training period lasting 6 months and 3 months, respectively [32][33][34]. Long-term effects were not measured in these three studies.…”
Section: Table 2 Mean (Sd) Of Groups and Mean (95% Ci) Difference Bet...mentioning
confidence: 83%